PENGARUH CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PERTAMBANGAN INDONESIA - Aditya, Mandala (UNIB Press, 2019)
This study aimed to analyze the effect of the mechanism of Corporate Governance (CG) and the disclosure of Corporate Social Responsibility (CSR) to corporate value. This type of research used in this research is the empirical research. The population in this study are all mining companies listed on the Stock Exchange in 2011-2015. The sampling technique used was purposive sample and selected 8 companies unit of analysis.Data analysis tools in this test using panel data regression analysis, which wants to see the effect of Managerial Ownership, Institutional Ownership, Proportion of Independent Commissioner, Number of Audit Committee and CSR Disclosure of the value of the Company. The results of this study indicate that the Institutional Ownership positive effect on firm value. Proportion of Independent Commissioner negatively affect the value of the company. Managerial Ownership, Number of Audit Committee and Disclosure of Corporate Social Responsibility (CSR) has no effect on the value of the company.